2017
DOI: 10.1021/acs.iecr.7b01405
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Algae Biocrude for a Low-Nitrogen-Containing Biofuel: Compositions, Intermediates, and Reaction Routes

Abstract: The upgrading of algae biocrude (obtained by hydrothermal liquefaction) was studied under mild conditions. Here we adopted a guard catalyst to protect the core catalyst and obtained algae biofuel with low heteroatom content at 350 °C. The nitrogen content of biofuel is 0.016 wt %, and the calculated oxygen content is less than 0.51 wt %. Furthermore, the effective yield from biocrude to a low-heteroatom-containing biofuel was close to the theoretical yield. Through a detailed study of the upgrading process, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Indole conversion was also observed in the reported set of experiments. Based also on literature [15], possible reaction products can be represented by ethylbenzene and ethylcyclohexane ( Figure 5), which were both detected among the reaction products. other studies [21,22], where different settings of the instruments were able to detect also other fatty acids up to C20.…”
Section: Key-compounds and Reactions Routesmentioning
confidence: 74%
See 1 more Smart Citation
“…Indole conversion was also observed in the reported set of experiments. Based also on literature [15], possible reaction products can be represented by ethylbenzene and ethylcyclohexane ( Figure 5), which were both detected among the reaction products. other studies [21,22], where different settings of the instruments were able to detect also other fatty acids up to C20.…”
Section: Key-compounds and Reactions Routesmentioning
confidence: 74%
“…Other studies in the literature were conducted with different catalysts and operating conditions, such as: ZSM-5 zeolites [10], sulfided NiMo and CoMo on Al2O3 support [11], Pt/Al2O3 and HZSM-5 [12] and several other supported metallic catalysts [13]. Two-stage upgrading has been investigated as well [14,15]. A few hydrotreating studies are also available for wood biocrude.…”
mentioning
confidence: 99%
“…This suggests that only adjusting the condition parameters and adding catalysts is not enough to achieve complete N removal. Despite the existence of bio-oil upgrading treatments such as hydrotreating [12] and distillation [13], which could reduce the N content in the bio-oil, these are extremely cost-intensive processes, especially the former, due to their employment of H 2 . Moreover, bio-oil obtained from HTL can contain water, which is difficult to remove during solvent extraction, being one of the mentioned causes for deactivation of upgrading sulfide catalysts [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have been performed on the hydrotreatment of HTL biocrude from algae in the presence of different catalysts [22][23][24][25], where the focus was on achieving a high degree of heteroatoms removal. Zhao et al [26,27] investigated the catalytic upgrading of algae biocrude in two-stage batch experiments, and reported almost complete removal of N (99.5%) in the presence of a commercial NiMo/γ-Al 2 O 3 catalyst. Cole et al [28] successfully carried out two-stage upgrading for macroalgae biocrude and reported it as the only viable way to effectively achieve drop-in fuels.…”
mentioning
confidence: 99%